Impact of Occupational Stress and Coping Styles on Burnout among Physicians in Yun Nan, China - Zhi Lin, Wang; Ho, Robert (Scholar: Human Sciences, 2016)
This study was conducted to investigate the impact of occupational stress and coping styles on burnout among physicians in Yun Nan province, China. The sample consisted of 208 participants, consisting of 80 male and 128 female in-service physicians, recruited from different public hospitals. They voluntarily filled in a survey questionnaire consisting of the Occupational Stress Indicator-2 (OSI-2), the Maslach Burnout Inventory-Human Services Survey (MBI-HSS), and the Coping Inventory for Stressful Situations (CISS). The results revealed that the Chinese physicians’ reported level of occupational stress directly influenced their reported level of burnout. It was also found that the more they applied emotion-focused coping, the higher was their reported level of burnout. Their reported level of occupational stress was not found to have any significant influence on their employment of either problem-focused or avoidance-focused coping style. All three coping styles were found to be associated with burnout. The more the participants employed problem-focused coping style as well as emotion-focused style, the higher was their reported level of burnout. On the other hand, the more they employed avoidance-focused coping style the lower was their reported level of burnout.